A Practical Guide to Dragons - Trumbauer, Lisa 1963- (Renton, WA : Wizards of the Coast, 2006)
Presents the mythical world of dragons, describing their anatomy, language, rules of combat, life span, society, and the characteristics of the different types of dragons.
Keywords: Dragons